Flexibilidad cognitiva, memoria de trabajo y control inhibitorio en adolescentes deportistas y adolescentes que no practican deporte (2023)
Physical activity from childhood and throughout adulthood helps to maintain a reduced risk of various physical and mental diseases. The aim of this study was to establish whether there are significant differences in cognitive flexibility, working memory and inhibitory control in sport populations and disciplines, through the application of three neuropsychological instruments. The research was non-experimental with a quantitative approach in an empirical-analytical paradigm, with a population of 60 adolescents and a sample of 30 adolescent athletes and 30 non-sporting adolescents. The statistical analysis was carried out using the SPSS program,